Cultural imperialism of the North? The expansion of the CBC Northern Service and community radio - MacLennan, Anne (Radio Journal:International Studies in Broadcast & Audio Media, 2011)
Postprint upload. Radio broadcasting spread quickly across southern Canada in the 1920s and 1930s through the licensing of private independent stations, supplemented from 1932 by the Canadian Radio Broadcasting Commission and by its successor, the Canadian Broadcasting Corporation, from 1936. Broadcasting in the Canadian North did not follow the same trajectory of development. The North was first served by the Royal Canadian Corps of Signals that operated the Northwest Territories and Yukon Radio System from 1923 until 1959. The northern Canadian radio stations then became part of the CBC. This work explores the resistance to the CBC Northern Broadcasting Plan of 1974, which envisaged a physical expansion of the network. Southern programming was extended to the North; however, indigenous culture and language made local northern programmes more popular. Efforts to reinforce local programming and stations were resisted by the network, while community groups in turn rebuffed the network’s efforts to expand and establish its programming in the North, by persisting in attempts to establish a larger base for community radio.